1993
DOI: 10.1017/s0142716400009565
|View full text |Cite
|
Sign up to set email alerts
|

Bilingual and monolingual children's use of two lexical acquisition heuristics

Abstract: Children's heuristics for word learning have been the focus of much research, but little is known about bilinguals' and monolinguals' comparative use of them. In this study, 36 Serbian/ English bilinguals and 42 English monolinguals, who were between 5 and 8 years old and lived in the same neighborhoods in the United States, received a successive name training assessment of two heuristics: criterial use of highlighted features and preservation of mutual exclusivity. Older children employed both heuristics more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 28 publications
2
47
0
Order By: Relevance
“…Because the PPVT has not been standardized for Urdu, we were unable to determine the age level of the children's vocabulary. The Wnding that bilingual children knew English better than Urdu is consistent with past studies that have shown a similar advantage for English (Bialystok, ShenWeld, & Codd, 2000;Davidson et al, 1997;Merriman & Kutlesic, 1993). In fact, it is possible that these diVerences would have been greater for the older children if the PPVT had been administered beyond Plate 50.…”
Section: Language Proficienciessupporting
confidence: 85%
See 4 more Smart Citations
“…Because the PPVT has not been standardized for Urdu, we were unable to determine the age level of the children's vocabulary. The Wnding that bilingual children knew English better than Urdu is consistent with past studies that have shown a similar advantage for English (Bialystok, ShenWeld, & Codd, 2000;Davidson et al, 1997;Merriman & Kutlesic, 1993). In fact, it is possible that these diVerences would have been greater for the older children if the PPVT had been administered beyond Plate 50.…”
Section: Language Proficienciessupporting
confidence: 85%
“…Although monolingual and bilingual adults have been found to use mutual exclusivity to the same extent in language-learning situations (Au & Glusman, 1990), at least several studies have found diVerences in monolingual and bilingual children's use of language-learning principles, particularly those based on mutual exclusivity (e.g., Davidson et al, 1997;Merriman & Kutlesic, 1993). For example, Davidson and colleagues (1997) found that monolingual 6-year-olds were more likely than their bilingual peers to use mutual exclusivity rules on ambiguous and rejection tests.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations